Semiglobal Finite-Time Synchronization of Complex Dynamical Networks via Periodically Intermittent Control. (20th May 2015) - Fan, Yihan; Liu, Hongmei; Mei, Jun
Abstract : This paper studies the finite-time synchronization problem for a class of complex dynamical networks by means of periodically intermittent control. Based on some analysis techniques and finite-time stability theory, some novel and effective finite-time synchronization criteria are given in terms of a set of linear matrix inequalities. Particularly, the previous synchronization problem by using periodically intermittent control has been extended in this paper. Finally, numerical simulations are presented to verify the theoretical results.